Adobe Creative Suite 2 - Golding, Mordy (Indianapolis, Ind. : Sams, 2006)
Adobe's Creative Suite brings together the Photoshop, Illustrator, Acrobat, InDesign, and GoLive software, and a new file management tool called Version Cue.
Includes index.
Keywords: Computer graphics; Desktop publishing; Web sites -- Design